Integrating the Kano model with NSD and EMF to assess the innovative attributes of service quality – an empirical study of Taiwan's KTV service industry. Issue 4 (1st October 2016) - Lo, Ta-Sheng; Wei, Hsiao-Lan; Lu, Hsi-Peng; Ko, Hsien-Tang
Abstract: Innovative services can enhance the competitiveness and market share of KTV (Karaoke TeleVision) operators by extending the services of their In-store customers to their In-house customers via cloud services. The purpose of this paper is to determine the innovative service attributes of the KTV service model. The study proposed the Kano model, combining new service development (NSD) with an Experience Marketing Framework (EMF). Finally, customer satisfaction was analyzed. The study found that there are 14 attributes of attractive requirements, two attributes of one-dimensional requirements and three attributes of indifference requirements. When the 400 general customers were divided in two groups ('gender' and 'have used/not used'), 18 of the attributes were the same. The only different attribute between the two groups is the sharing platform item, which is an attractive attribute for females and an indifference attribute for males. This was also an attractive attribute for people who 'have used' and an indifference attribute for people who 'have not used'. Based on these findings, the study provides five practical implications that can serve as a guideline for KTV operators, providing them a useful reference for designing innovative services.